Analyse des erreurs grammaticales dans les compétences d’écrite des étudiants de niveau débutants du deuxième semestre de la section de la pédagogie du français - Stefany Jogi Simamora; Ria Fitrasih (Universitas Negeri Semarang, 2024)
This study aims to find out what types of grammatical writing errors are made by AI-level language education students. The method used in this research is descriptive qualitative. The benefits of this study are to add insight and knowledge to researchers about writing a study on grammatical error analysis of French writing skills. In this study, the data source was taken from the results of students writing taken from the results of the final semester exam, and the results of the form filling. The results showed that there were 124 errors in exercise 1 and 84 errors in exercise 2, including omission of orthography, excessive orthography, malformations, and mail order. The most dominating errors are malformations.